Estudio comparativo de herramientas de Software ERP para Pymes y grandes empresas. - Hurtado Borja, Carlos Joel (2023)
This document focuses on the comparative study of ERP software tools for SMEs and large companies. The main objective of the study is to analyze and compare different ERP software tools, in order to identify the advantages and disadvantages of each tool and provide a guide for decision making in the selection of an appropriate tool. To carry out the study, a bibliographic review was carried out and information on ERP software tools was collected. ERP software tools for large companies were found to be more expensive and require more resources to implement and maintain than ERP software tools for SMBs. However, ERP software tools for large companies offer greater scalability and customization. It is concluded that there is no single ERP software tool that is suitable for all companies, and that the selection of a tool should be based on the specific needs and characteristics of each company. The study provides valuable information for business owners and managers considering implementing an ERP software tool.